Billions. Season six [videorecording (DVD)] - Koppelman, Brian; Levien, David; Sorkin, Andrew Ross (Paramount, 2022)
In season six, the dust clears to reveal a world that has evolved. With Axe gone and Michael Prince assuming his place, Chuck must develop a new strategy that is keener and more sophisticated than before. All the players, from Wags to Wendy, from Taylor to Sacker, and of course Senior, must sharpen their weapons and look for new alliances in order to survive. The ground is ever shifting and the stakes absolute in this four-disc collection that includes every thrilling episode, along with an exclusive featurette and more. New king, new war, new rules.